Do Italians Communicate it Better? Exploring Public Organizations Professionals’ Skills in Learning Environments - Capolupo, Nicola; Bottoni, Gianmaria (Italian Sociological Review, 2022)
The outbreak of the COVID-19 pandemic has dramatically altered the way organizations work, as well as technologies, skills and knowledge required to adopt these new disruptive methodologies. While firms have found themselves prepared to cope with this need because more sensitive to their employee’s digital competences, this considerably differs for public organizations, where turnover and professional trainings are often delayed or non-existent. These difficulties particularly occur in communication sector, where professionals must keep up with several threats in an unstable scenario. The role played by digital techniques in this critical period has brought new forms of knowledge exchange among both professionals and scholars, spurring new methods of inquiry in qualitative and exploratory research. The aim of this article is to investigates which are the new digital communication skills required to professionals in public organizations, and what issues arise in acquiring or applying them during the working daily life. To meet this goal, a digital focus group on Microsoft Teams among professional communicators from public organizations was carried out. The findings of the focus group have been discussed to address a twofold need: mapping hard and soft skills of digital communicators in Public Administration; evaluate the relevance of virtual focus groups in organizational studies within the pandemic scenario.